(untitled) (Stavební obzor - Civil Engineering Journal, 2023)
The article focuses on the design and implementation of a Low-cost GNSS device for autonomous position monitoring and for determining parameters of the atmosphere. The first part is dedicated to the specification of individual components and their combination into several devices. The primary part includes a test of these GNSS devices and the parameters of data collection. This is followed by a quality test of these collected datasets, in several graphs is shown device capabilities. Also, we can see some problems with components, but we were able to specify what causes them. The final part deals with positioning and determining atmospheric parameters by G-Nut software with the selected GNSS sensor.